The dissemination and implementation of national asthma guidelines in South Africa: The use of outcome mapping - Bob Mash; G. Ainslie; Elvis Irusen; A. Bheekie (South African Family Practice)
Asthma is an important chronic inflammatory disorder with significant morbidity and mortality in South Africa. The development of national asthma guidelines by the South African Thoracic Society and National Asthma Education Programme has been one approach to try and improve the quality of care. The effectiveness of previous guidelines has been limited by the lack of an effective approach to dissemination, implementation and evaluation. The newly revised guidelines will be completed in 2007 and this paper outlines how Outcome Mapping has been used to create a detailed and comprehensive approach to bridging the gap between the guidelines and clinical practice.